Malignant ventricular tachycardia in acromegaly: a case report - An, Zhe (2015)
CONTEXT: In patients with acromegaly, cardiovascular complications are the main cause of death; sudden death has been associated with ventricular tachyarrhythmias. In other patients with life-threatening ma-lignant ventricular tachyarrhythmias, surgical placement of an implantable cardioverter-defibrillator (ICD) has proved highly effective in reducing sudden death rates. CASE REPORT: The present article reports the case of a 50-year-old male acromegalic patient who pre-sented symptoms of syncope induced by ventricular tachycardia. An ICD was surgically implanted and a pituitary adenoma, which was responsible for the acromegaly, was completely removed in the same procedure. The surgery was successful and the ventricular arrhythmias were effectively terminated. During six months of follow-up, no documented arrhythmic episodes occurred. CONCLUSION: In patients with acromegaly, malignant ventricular tachyarrhythmia might be effectively controlled by implantation of an ICD and surgical removal of the pituitary adenoma.